Geology, geochemistry and magnetic petrology of Archean granitoids of the northeastern portion of Água Azul do Norte, Carajás Province - Gabriel, Eleilson Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
Teses